ЛИНГВОДИДАКТИЧЕСКАЯ ХАРАКТЕРИСТИКА УЧЕБНЫХ СЛОВАРЕЙ КОМПЛЕКСНОГО ТИПА - Каллибекова, Г.А. (SCIENCE and SOCIETY, 2024)
The article comprehensively describes the importance of complex dictionaries, that is, the Russian language dictionary, in the educational process. Also, the importance of the Russian language dictionary as an effective tool for teaching vocabulary is emphasized.